Effect of concurrent resistance and endurance training on physiologic and performance parameters of well-trained endurance cyclists - Levin, G. T.; McGuigan, M. R.; Laursen, P. B. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to investigate the effect of concurrent resistance and endurance cycle training on physiologic and performance parameters of cyclists. Before and after a 6-week training intervention period, 14 well-trained male cyclists completed a maximal graded exercise test, a 30-km dynamic cycling test with 3 intermittent 250-m and 1-km sprints, and a 1 repetition maximum (1RM) squat test for the assessment of lower-limb strength. Subjects were allocated into 2 groups: a resistance training group (RT; n = 7) that completed a 6-week undulating, periodized resistance training program (3/wk) in conjunction with their regular cycle training and a control group (CON; n = 7) that maintained their usual cycle training. Upon completion of the training intervention, there was no change in graded exercise test parameters in either group, but the RT group showed a significantly greater increase in 1RM squat strength compared with CON (p < 0.05). Moreover, the change in 30-km time trial and sprinting performance did not differ between RT and CON, except for the final 1-km sprint where the percent change in 1-km final sprint performance was greater in CON (+11%) compared with RT (-5%). In conclusion, although concurrent resistance and endurance training in well-trained cyclists enhanced 1RM strength, it did not improve overall cycle time trial performance and in fact was shown to reduce 1-km final cycle sprint performance compared with a CON group performing their normal cycle training.